1995
DOI: 10.1109/55.388720
|View full text |Cite
|
Sign up to set email alerts
|

Highly suppressed boron penetration in NO-nitrided SiO/sub 2/ for p/sup +/-polysilicon gated MOS device applications

Abstract: Absfruct-In this paper, we demonstrate the superior diffusion barrier properties of NO-nitrided SiOn in suppressing boron penetration for p+-polysilicon gated MOS devices. Boron penetration effects have been studied in terms of flatband voltage shift, decrease in inversion capacitance (due to polysilicon depletion effect), impact on interface state density, and chargeto-breakdown. Results show that NO-nitrided SiOz, as compared to conventional thermal SiOz, exhibit much higher resistance to boron penetration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…[4][5][6][7][8] Nitridation processes have been proposed to reduce the boron penetration into the gate oxide, such as nitrogen implantation, NH 3 , N 2 O, and NO annealing. [9][10][11] In previous works, we have proposed an original solution by the insertion of a nitrogen-doped layer (NIDOS) between the polySi gate and the insulator. [12] The main advantages of this two-layer gate engineering approach are controlling the nitrogen concentration in the 4-nm-thick NIDOS layer during the LPCVD deposition and the large grain size of the amorphous as-deposited silicon film at low temperature with disilane gas source.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Nitridation processes have been proposed to reduce the boron penetration into the gate oxide, such as nitrogen implantation, NH 3 , N 2 O, and NO annealing. [9][10][11] In previous works, we have proposed an original solution by the insertion of a nitrogen-doped layer (NIDOS) between the polySi gate and the insulator. [12] The main advantages of this two-layer gate engineering approach are controlling the nitrogen concentration in the 4-nm-thick NIDOS layer during the LPCVD deposition and the large grain size of the amorphous as-deposited silicon film at low temperature with disilane gas source.…”
Section: Introductionmentioning
confidence: 99%
“…Nitridation of the gate oxide is feasible. [9][10][11][12] This can be achieved by nitridation of the gate and/or gate oxide using N 2 O, NO oxidation or annealing, which a nitrogen layer was found to incorporate at the SiO 2 /Si interface as a barrier to retard the boron diffusion. 12 In this letter, a novel and simple process of building the nitrogen diffusion barrier between the oxide and poly-Si was developed by using an inductivecoupling-nitrogen-plasma ͑ICNP͒ process.…”
Section: S Chao A) and C H Chu B)mentioning
confidence: 99%
“…Many methods have been proposed to suppress boron penetration. [6][7][8][9][10][11][12] The first way is to retard the boron diffusion inside the poly-Si. The stacked or modified structures of the poly-Si gate have been proposed.…”
Section: S Chao A) and C H Chu B)mentioning
confidence: 99%
“…It has been shown that when nitrogen is incorporated into the gate oxide, its concentration peaks at the SiOz/Si interface [1][2][3][4]. This nitrogen-rich layer has higher dielectric constant and smaller bandgap than the bulk Si02 [5].…”
Section: B Proposed Enhanced Degradation Modelmentioning
confidence: 99%